Socialization and Workshop for Office Renovation RW 01-RW 06 in Kebon Pala Village, East Jakarta - Ulinata; Grace Putri Dianty; Susan M. Nainggolan; Edward Surya Wijaya; Situmorang Lumay Bintang (Jurnal Pengabdian Masyarakat Bestari, 2023)
The community service activity carried out by the UKI Architecture Study Program has the theme "Green Action 27: Socialization and Training (Workshop) for RW Office Space Renovation in Kebon Pala Village, East Jakarta City." This activity aims to educate the public about the surgery of office space so that they can create a comfortable and aesthetically pleasing workspace that increases work productivity for its users but does not cost a fortune. The method is to hold outreach and workshops. The process is that the participants practice directly by making a room overhaul using existing furniture and the addition of unused items, which creates a more aesthetic and comfortable office space. As a result, participants can get additional education and understand the material presented. To increase the enthusiasm of the participants, a competition is held so that their level of understanding is known.